Perawatan Diri Selama Menstruasi pada Remaja Putri di SMA Negeri 10 Palangka Raya - Riny Natalina; Wahidah Sukriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Teenage is a time when someone transitioned from childhood to adulthood characterized by various changes both physically, cognitively, socially and emotionally. Among them is Puberty, puberty causes adolescents to have special needs for hygiene. One of the important things to pay more attention to is self-care, especially during menstruation. In adolescent girls, puberty is characterized by one of the first menstrual periods or also called menarche. Personal Hygiene menstruation is a critical issue as a determinant of the health status of adolescents who will influence the life of old age. Poor personal hygiene has a major effect on morbidity and complications. Familiarize yourself with hygienic behavior. Hygienic behavior during menstruation will not happen as well, but it is a learned process because individuals understand the positive or negative effects of behavior related to menstruation. Reproductive health education is basically an effort to provide knowledge about the functions, systems, and processes of reproduction as a result of human growth and development. At the same time establishing morals, ethics and building a commitment to avoid misuse of the reproductive organs. The Youth Information and Counseling Center (PIK-R) is a program which is developed from, by and for adolescents where one of the activities in it is providing information about adolescent reproductive health